Organic coffee under perspective of energy efficiency - Turco, Patrícia Helena Nogueira; Bueno, Osmar de Carvalho [UNESP]; Esperancini, Maura Seiko Tsutsui [UNESP]; Bliska, Flávia Maria de Mello (My University, 2014)
The energy analysis development in this study contributes to the understanding of the dynamics of the organic coffee productive system, in particular to assess the independence of this system with respect to the use of industrialized input products. Thus, it provides information about the sustainability of that production system. Technical itineraries used in this study consist of energy expenditure made with coffee cultivation, according to the type, source and form of energy inputs, agricultural machines, equipment and labor force used in that production system. The energy expenditure, converted into energy units, quantified the input energy. And the organic coffee production, measured in kilograms of processed coffee beans, was the output energy. Primary data used in this study were obtained from organic coffee producers in the Southern region of Minas Gerais State, Brazil, in 2011. Energy balance identified was positive, since the estimated output energy was 626.465 MJ/ha and the energy expenditure was 112.998 MJ/ha, during the useful life of the crop.
Keywords: Energetic balance; Sustainable production; Coffee cultivation